2017
DOI: 10.1080/2162402x.2017.1322242
|View full text |Cite
|
Sign up to set email alerts
|

A circulating TH2 cytokines profile predicts survival in patients with resectable pancreatic adenocarcinoma

Abstract: Surgery is the only potentially curative option for patients with pancreatic ductal adenocarcinoma (PDAC), but metastatic relapse remains common. We hypothesized that the expression levels of inflammatory cytokines could predict recurrence of PDAC, thus allowing to select patients who most likely could benefit from surgical resection.We prospectively collected plasma at diagnosis from 287 patients with pancreatic resectable neoplasms. The expression levels of 23 cytokines were measured in 90 patients with PDAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…helper T lymphocytes (CD3 + CD4 + cells), regulatory T lymphocytes (CD3 + CD4 + CD25 + FoxP3 + cells, Tregs), B lymphocytes (CD3 − CD19 + cells), regulatory B cells (CD3 − CD19 + CD25 + FoxP3 + cells, Bregs), myeloid-dendritic cells (CD11b + CD11c + HLA-DR + cells, DCs), plasmacitoid DCs (CD11b + CD11c − CD123 + , pDCs), macrophages (CD 14 + HLA-DR + CD68 + CD206 + cells), granulocytes (PMNs, CD14 − CD15 + CD11b + cells) as well as two MDSC subsets: e-MDSCs (Lin − HLA-DR − CD11b + CD33 + cells) and M-MDSCs (CD14 + HLA-DR −/lo cells) (Additional file 1: Figure S1). Notably, we found that PDAC tissues have a higher CD45 + cell infiltrate than their normal counterpart, likely reflecting the ability of the tumor or surrounding stroma to release soluble factors attracting immune cells [20,21] (Fig. 1b), supporting the concept that PDAC is a tumor with an immune-hostile tumor microenvironment [24].…”
Section: Resultssupporting
confidence: 57%
“…helper T lymphocytes (CD3 + CD4 + cells), regulatory T lymphocytes (CD3 + CD4 + CD25 + FoxP3 + cells, Tregs), B lymphocytes (CD3 − CD19 + cells), regulatory B cells (CD3 − CD19 + CD25 + FoxP3 + cells, Bregs), myeloid-dendritic cells (CD11b + CD11c + HLA-DR + cells, DCs), plasmacitoid DCs (CD11b + CD11c − CD123 + , pDCs), macrophages (CD 14 + HLA-DR + CD68 + CD206 + cells), granulocytes (PMNs, CD14 − CD15 + CD11b + cells) as well as two MDSC subsets: e-MDSCs (Lin − HLA-DR − CD11b + CD33 + cells) and M-MDSCs (CD14 + HLA-DR −/lo cells) (Additional file 1: Figure S1). Notably, we found that PDAC tissues have a higher CD45 + cell infiltrate than their normal counterpart, likely reflecting the ability of the tumor or surrounding stroma to release soluble factors attracting immune cells [20,21] (Fig. 1b), supporting the concept that PDAC is a tumor with an immune-hostile tumor microenvironment [24].…”
Section: Resultssupporting
confidence: 57%
“…including healthy volunteers and patients with pancreatic cancer with resectable, locally advanced or metastatic disease, IL8 levels were higher in patients with cancer than in healthy controls but were not associated with survival differences (35). More recently, we conducted the most comprehensive profiling of cytokines in the largest prospective cohort of patients with resectable pancreatic cancer to date and IL8 had no prognostic value in this cohort of patients (36). Excluded a prognostic role for IL8, we acknowledge that its negative predictive value could be although extended also to other cytotoxic agents different from nal-IRI that induce in pancreatic cancer cells a proapoptotic stimuli by which a TAK1 activation mirrored by IL8 could protect.…”
Section: Discussionmentioning
confidence: 99%
“…T h 2 lymphocytes help B cells produce antibodies and suppress the action of cytotoxic T cells [16]. Intriguingly, a low circulating level of IL-4 can identify resectable pancreatic adenocarcinoma patients with better prognosis [32].…”
Section: T Cellsmentioning
confidence: 99%